Interactive Community Mapping : Improving Service Delivery and Empowering Communities - Shkabatur, Jennifer; Kumagai, Saki (World Bank, Washington, DC, 2014)
Mapping presents a compelling way to demystify complex data and concepts into useful visual information that most people can understand regardless of language, level of literacy, or culture. These maps can also be shared instantaneously with the world via the Internet. Interactive community mapping (ICM) is one method of information and communication technology (ICT)-enabled participatory mapping. In the development context, ICM can be a useful approach in helping community members, members of civil society organizations (CSOs), governments, and development partners to better picture and assess the needs and concerns of the mapped communities and adjust development plans, activities, and policies accordingly. This note is aimed at providing step-by-step guidance on the design and implementation of the ICM process to achieve an evidence-based and increasingly participatory decision-making approach for development projects. Relying on good practice examples from Kenya and Tanzania, this note seeks to provide a better understanding of how the potential benefits of ICM can be translated into tangible results. The note outlines some of the available ICM technology, delineate the enabling environment for ICM, and provide step-by-step guidance on how to effectively design and implement ICM in projects.